2018
DOI: 10.11604/pamj.2018.30.4.14765
|View full text |Cite
|
Sign up to set email alerts
|

Pied diabétique: aspects épidémiologique, diagnostique, thérapeutique et évolutif à la Clinique Médico-chirurgicale du CHU Sylvanus Olympio de Lomé

Abstract: IntroductionLe pied diabétique est une complication fréquente et grave du diabète. Le but de cette étude est de déterminer le profil épidémiologique, diagnostique, thérapeutique et évolutif du pied diabétique en milieu hospitalier à Lomé (Togo)MéthodesEtude rétrospective descriptive réalisée du 1er janvier 2011 au 31 décembre 2015 (5 ans) à la clinique médico-chirurgicale du CHU Sylvanus Olympio de Lomé. Etaient inclus dans l'étude, toute patiente hospitalisée pendant la période d'étude pour pied diabétique.Ré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
2
9
0
Order By: Relevance
“…Patients were then seen at an advanced stage of lesions as found in our study: 87% in Texas 3D stage or 52% in Wagner grades 4 and 5 with a very high risk of amputation. TIENO [11] in Burkina Faso had also found in his study foot lesions classified mainly in grades 4 and 5 by Wagner and the same observation had recently been made by Djibril et al [9] in Togo in 2018. The main reason for the delay to hospital recourse by diabetic patients was fear of amputation (47.8% of cases).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Patients were then seen at an advanced stage of lesions as found in our study: 87% in Texas 3D stage or 52% in Wagner grades 4 and 5 with a very high risk of amputation. TIENO [11] in Burkina Faso had also found in his study foot lesions classified mainly in grades 4 and 5 by Wagner and the same observation had recently been made by Djibril et al [9] in Togo in 2018. The main reason for the delay to hospital recourse by diabetic patients was fear of amputation (47.8% of cases).…”
Section: Discussionsupporting
confidence: 74%
“…In our study, patients had a particularly long itinerary before having recourse to the referral centre, with an average consultation period of 44 days in our study. This long period of consultation in specialized environment has been re-Journal of Diabetes Mellitus ported by Djibril et al [9] who had found an average of 33 days consultation with extremes from 6 to 120 days. The painless nature of the initial lesions and socio-economic factors (32.5% of the reasons found in our work) can be incriminated.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The mean age was 42.66 years, other African studies: Sani, R. et al [6], Nghario, L. et al [7], Guèye, D.D. et al [8], Sano, D. et al [9], Djibril, A.M. et al [10] found respectively 53 years, 54 years, 57 years, 58.9 years, 60.74 years. The majority of our patients were not in school with 54.3%.…”
Section: Discussionmentioning
confidence: 84%
“…Diabetes is the aetiology of micro and macrovascular complications that lead to foot lesions [ 6 ]. Diabetic foot is defined as any infection, ulceration, or destruction of the deep tissues of the foot associated with neuropathy and/or peripheral arterial disease of the lower limbs in diabetic patients [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%